Analysis of essential pathways for self‐renewal in common marmoset embryonic stem cells. Issue 1 (21st February 2014) - Nii, Takenobu; Marumoto, Tomotoshi; Kawano, Hirotaka; Yamaguchi, Saori; Liao, Jiyuan; Okada, Michiyo; Sasaki, Erika; Miura, Yoshie; Tani, Kenzaburo
Abstract : Common marmoset (CM) is widely recognized as a useful non‐human primate for disease modeling and preclinical studies. Thus, embryonic stem cells (ESCs) derived from CM have potential as an appropriate cell source to test human regenerative medicine using human ESCs. CM ESCs have been established by us and other groups, and can be cultured in vitro . However, the growth factors and downstream pathways for self‐renewal of CM ESCs are largely unknown. In this study, we found that basic fibroblast growth factor (bFGF) rather than leukemia inhibitory factor (LIF) promoted CM ESC self‐renewal via the activation of phosphatidylinositol‐3‐kinase (PI3K)‐protein kinase B (AKT) pathway on mouse embryonic fibroblast (MEF) feeders. Moreover, bFGF and transforming growth factor β (TGFβ) signaling pathways cooperatively maintained the undifferentiated state of CM ESCs under feeder‐free condition. Our findings may improve the culture techniques of CM ESCs and facilitate their use as a preclinical experimental resource for human regenerative medicine. Abstract : Self‐renewal of common marmoset embryonic stem cells (CM ESCs) is promoted by bFGF. bFGF activates the PI3K‐AKT pathway in CM ESCs on feeder cells. bFGF and TGFβ in combination support culture of CM ESCs without feeder cells. CM ESCs show phenotypes similar to those of human ESCs and mouse epiblast SCs.